The Significance of Duration and Amount of Sodium Reduction Intervention in Normotensive and Hypertensive Individuals: A Meta-Analysis(1)(2) - Graudal, Niels (Adv Nutr, 2015)
The purpose of this meta-analysis was to establish the time for achievement of maximal blood pressure (BP) efficacy of a sodium reduction (SR) intervention and the relation between the amount of SR and the BP response in individuals with hypertension and normal BP. Relevant studies were retrieved from a pool of 167 randomized controlled trials (RCTs) published in the period 1973–2010 and integrated in meta-analyses. Fifteen relevant RCTs were included in the maximal efficacy analysis. After initiation of sodium reduction (range: 55–118 mmol/d), there were no significant differences in systolic blood pressure (SBP) or diastolic blood pressure (DBP) between measurements at weeks 1 and 2 (∆SBP: −0.18 mmHg/∆DBP: 0.12 mmHg), weeks 1 and 4 (∆SBP: −0.50 mmHg/∆DBP: 0.35 mmHg), weeks 2 and 4 (∆SBP: −0.20 mmHg/∆DBP: −0.10 mmHg), weeks 2 and 6 (∆SBP: −0.50 mmHg/∆DBP: −0.42 mmHg), and weeks 4 and 6 (∆SBP: 0.39 mmHg/∆DBP: −0.22 mmHg). Eight relevant RCTs were included in the dose-response analysis, which showed that within the established usual range of sodium intake [<248 mmol/d (5700 mg/d)], there was no relation between the amount of SR (range: 136–188 mmol) and BP outcome in normotensive populations [∆SBP: 0.99 mm Hg (95% CI: 2.12, 4.10), P = 0.53; ∆DBP: −0.49 mm Hg (95% CI: −4.0, 3.03), P = 0.79]. In contrast, prehypertensive and hypertensive populations showed a significant dose-response relation (range of sodium reduction: 77–140 mmol/d) [∆SBP: 6.87 mmHg (95% CI: 5.61, 8.12, P < 0.00001); ∆DBP: 3.61 mmHg (95% CI: 2.83, 4.39, P < 0.00001)]. Consequently, the importance of kinetic and dynamic properties of sodium reduction, as well as baseline BP, should probably be considered when establishing a policy of sodium reduction.